The Role of Nursing in Advancing Healthcare Quality and Patient Safety: A Comprehensive Review of Evidence-Based Practices and Systemic Impacts - Alwuthaynani, Jawaher Habaylis; Barnawi, Kulthum Zakaria; Alneami, Waad Yahya; Alresheedi, Afaf Ibrahim; Altamimi, Omar Salem; Al-Jaloud, Abdulaziz Saleh Fahd; Alshammeri, Eida Habeeb; Alanazi, Maryam Saad Mubhil; Altamimi, Salem Mansour Zaid; Alshammry, Aydah Habib (Journal of Posthumanism, 2024)
Nursing plays a pivotal role in shaping healthcare quality and advancing patient safety, positioning nurses as central agents of systemic transformation within global health systems. As the largest segment of the healthcare workforce, nurses contribute directly to patient outcomes through the consistent application of evidence-based practices (EBPs), fostering a culture of safety, and strengthening interprofessional collaboration. This review synthesizes research from 2016 to 2025, examining how nursing interventions, leadership, and policy engagement advance care quality and safety. Evidence highlights that nursing-led initiatives reduce medical errors, improve patient satisfaction, and enhance efficiency in care delivery. Furthermore, systemic impacts—such as nurse participation in policy development, adoption of digital health innovations, and leadership in safety culture—extend nursing’s influence beyond bedside care to organizational transformation. Challenges including workforce shortages, burnout, and disparities in resources across regions remain significant barriers, yet opportunities exist in technology integration, continuous professional development, and global policy support. By consolidating findings across multiple domains, this review underscores nursing’s indispensable role in advancing healthcare quality and safety, while calling for sustained investment in nursing education, leadership, and evidence-based practice frameworks to ensure resilient, patient-centered health systems.